2015
DOI: 10.1063/1.4919005
|View full text |Cite
|
Sign up to set email alerts
|

High hole concentration in p-type AlGaN by indium-surfactant-assisted Mg-delta doping

Abstract: High hole concentration was achieved in Mg-doped AlxGa1−xN (x ∼ 0.4) by using indium-surfactant-assisted delta doping method. A maximum carrier concentration of 4.75 × 1018 cm−3 was obtained, which is three times higher than that of the conventionally delta-doped sample. Sheet resistivity as low as 2.46 × 104 Ω/sq was realized, benefiting from the high hole concentration (p). Analysis results show that the Mg incorporation is effectively enhanced, while the compensation ratio and acceptor activation energy (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 20 publications
0
61
0
Order By: Relevance
“…Technological advances in crystal growth showed that problems like the solubility limit, hydrogen passivation, and high defect ionization energies, hampering p-type conduction, can be overcome to some extent. [5][6][7] Doping by ion implantation offers several advantages over doping during growth especially for selective area doping as reported by Tadjer et al 8 Furthermore, the present generation of "white" LEDs, using a phosphor, suffers from efficiency problems. Recently, Lim et al proposed a phosphor-free white LED based on threedimensional gallium nitride structures.…”
mentioning
confidence: 98%
“…Technological advances in crystal growth showed that problems like the solubility limit, hydrogen passivation, and high defect ionization energies, hampering p-type conduction, can be overcome to some extent. [5][6][7] Doping by ion implantation offers several advantages over doping during growth especially for selective area doping as reported by Tadjer et al 8 Furthermore, the present generation of "white" LEDs, using a phosphor, suffers from efficiency problems. Recently, Lim et al proposed a phosphor-free white LED based on threedimensional gallium nitride structures.…”
mentioning
confidence: 98%
“…Therefore, numerous efforts have been undertaken to mitigate compensation by decreasing donor defects and increasing solubility of the dopants, increasing the hole mobility by reducing the scattering rate, and increasing the acceptor activation rate by reducing the activation energy through polarization field. The approaches include co-doping of Mg with Si or oxygen [102,103], Mg delta-doping [104,105], and Mg-doped AlxGa1-xN/AlN superlattice or AlxGa1-xN/AlyGa1-yN superlattice [106,107]. Some of the reports on the achievement of low p-type resistivities in high Al-molar fraction AlGaN are overviewed below.…”
Section: Doping Considerations In High Al-molar Fraction Alganmentioning
confidence: 99%
“…Therefore, numerous efforts have been undertaken to mitigate compensation by decreasing donor defects and increasing solubility of the dopants, increase the hole mobility by reducing the scattering rate, and increase the acceptor activation rate by reducing the activation energy through polarization field. The approaches include co-doping of Mg with Si or oxygen, [94,95] Mg delta-doping, [96,97] and Mg-doped AlxGa1-xN/AlN superlattice or AlxGa1-xN/AlyGa1-yN superlattice. [98,99] Some of the reports on the achievement of low p-type resistivities in high Al-molar fraction AlGaN are overviewed below.…”
Section: Doping Considerations In High Al-molar Fraction Alganmentioning
confidence: 99%